Web-Based Distance Learning Guidance Application in the Covid 19 Era: Aplikasi Bimbingan Belajar Jarak Jauh Pada Era Covid 19 Berbasis Web - Sagaf, Jusman A; Sumarno, Sumarno (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this research is to build a distance learning guidance information system in the era of covid 19. Therefor supporting technology facility is needed in creating a change in teaching and learning procedure into digital form that can be accessed online. The researcher took the initiative to implement learning guidance system using the distance method. The method used in this research is quantitative. The result that have been achieved in this research is to add insight into the latest information systems. The result of the research obtained resulted in a web-based distance learning guidance application system in the covid-19 era. The benefit of this research is that the application of distance learning guidance can make it easier for teacher and student to deliver material quickly. In the process of developing a web-based distance learning guidance system, using the PHP programming language version 7.3.27. Testing the system using the black box testing method to test the functional system so as to produce a system that works well.